2022
DOI: 10.1038/s41598-022-07877-y
|View full text |Cite
|
Sign up to set email alerts
|

Divergence time estimation using ddRAD data and an isolation-with-migration model applied to water vole populations of Arvicola

Abstract: Molecular dating methods of population splits are crucial in evolutionary biology, but they present important difficulties due to the complexity of the genealogical relationships of genes and past migrations between populations. Using the double digest restriction-site associated DNA (ddRAD) technique and an isolation-with-migration (IM) model, we studied the evolutionary history of water vole populations of the genus Arvicola, a group of complex evolution with fossorial and semi-aquatic ecotypes. To do this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…The allopatric divergence in the Ophrys aveyronensis we report here is indeed extremely recent compared to other species with disjunct geographic distributions in terrestrial systems (e.g. González-Serna, Cordero & Orego, 2018; Tomasello, Karbstein, Hodač, Paetzold & Hörandl, 2020; Wang et al, 2022; Cao et al, 2022; Balmori-de la Puente et al, 2022). It is likely to have arisen as a result of climate warming, not as a consequence of Quaternary climate fluctuations but as late as following the Last Glacial Maximum, which disrupted an ancestral geographic distribution and subsequently constrained the spatial dynamics of its subranges and does not a priori imply a human- induced biological introduction.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The allopatric divergence in the Ophrys aveyronensis we report here is indeed extremely recent compared to other species with disjunct geographic distributions in terrestrial systems (e.g. González-Serna, Cordero & Orego, 2018; Tomasello, Karbstein, Hodač, Paetzold & Hörandl, 2020; Wang et al, 2022; Cao et al, 2022; Balmori-de la Puente et al, 2022). It is likely to have arisen as a result of climate warming, not as a consequence of Quaternary climate fluctuations but as late as following the Last Glacial Maximum, which disrupted an ancestral geographic distribution and subsequently constrained the spatial dynamics of its subranges and does not a priori imply a human- induced biological introduction.…”
Section: Discussionsupporting
confidence: 53%
“…The allopatric divergence in the Ophrys aveyronensis species complex we report here is extremely recent compared to other species complex harboring disjunct geographic distribution in terrestrial (e.g. González-Serna et al, 2018; Tomasello et al, 2020; Wang et al, 2022; Cao et al, 2022; Balmori-de la Puente et al, 2022) or marine systems (Schmid et al, 2023; Marcionetti et al, 2023). It is likely to have arisen because of climate warming that dissected an ancestral geographic distribution and subsequently constrained the spatial dynamics of its subranges and does not a priori imply a human-induced biological introduction.…”
Section: Discussionmentioning
confidence: 55%
“…Since sonication is not used in ddRAD library preparation, this is not an issue with the ddRAD protocol. In fact, in other published ddRAD studies (e.g., Balmori‐de la Puente et al, 2022 ; Escoda et al, 2019 ), samples with an excess of C to A changes are either not found or are very rare and of small magnitude. Rather, the problem in the present work is likely to be related to the preservation of some samples.…”
Section: Discussionmentioning
confidence: 91%
“…The fossorial water vole, Arvicola scherman (former fossorial form of Arvicola terrestris = Arvicola amphibius ; for taxonomic considerations see Balmori-de la Puente et al (2022) and references therein) is a cricetid rodent that lives in extensive burrow systems and preferentially consumes roots, bulbs and tubers of dicotyledons and some Poaceae (Airoldi 1976). This species inhabits grasslands and orchards in the main mountain massifs of Europe, including the northern Iberian Peninsula, the Alps, the mountains of central Europe and the Carpathians, and is considered one of the most important agricultural pests in these areas (Somoano 2020).…”
Section: Introductionmentioning
confidence: 99%